Bioarchaeology of adaptation to a marginal environment in bronze age Western China. Issue 4 (25th January 2017) - Berger, Elizabeth; Wang, Hui
Abstract: Objectives: This study examines human adaptation to the 4000 BP climate change event, which is said to have increased the marginality of Inner Asian environments. We propose to define "marginal" environments not in relation to a specific economic activity (e.g., agriculture), but in relation to whether humans living there are physiologically stressed. Methods: Three sites in the Hexi Corridor of Gansu were studied, one from the early and two from the late Bronze Age (N = 125). The study includes three indicators of physiological stress: linear enamel hypoplasias (LEH); tibial periosteal lesions; and fertility. The early and late Bronze Age groups were compared to examine whether human physiological stress increased. Results: The percent of individuals with LEH declined dramatically, indicating fewer growth disruptions. Tibial periosteal reactions also changed, from mostly active to mostly healing at the time of death, indicating that frailty declined. Fertility, which is sensitive to changes in population health and resource availability, did not change significantly. Conclusions: Counter to the dominant narrative of environmental deterioration and subsistence system collapse, the Bronze Age residents of the Hexi Corridor show no skeletal evidence that they suffered from resource shortages or struggled to adapt in the fluctuating climate that pertained after the 4000 BP climate event. In fact, this study found that people suffered from less frailty and fewer growth disruptions after the unstable climate had persisted for some time. Therefore, in human biological terms, the Hexi Corridor did not become more marginal for human habitation during the Bronze Age.